Cardiac sarcoidosis : key concepts in pathogenesis, disease management, and interesting cases - Freeman, Andrew M.; Weinberger, Howard D. (Springer International Publishing Imprint: Springer, 2015)
Sarcoidosis remains an elusive diagnosis despite advanced technology available to clinicians in most major hospitals. Once diagnosed, the disease can be progressive and disabling or remain quiescent for years. It can affect any organ, but of course, one of the greatest concerns covered in this book is cardiac involvement that can lead to sudden death, arrhythmia, and heart failure, as well as many other complications. Cardiac Sarcoidosis is a clinician's field guide for diagnosing, managing, and treating the disease. Epidemiology, pathophysiology, and treatment options are reviewed with a strong clinical angle to provide high-yield and immediately implementable concepts at the bedside. Noting that there is no gold standard in diagnosing the disease or strong consensus on treatment options, the internationally renowned authors present evidence-based and balanced approaches and, in areas with little to no evidence, the emphasis is on providing best practice. This is an easy-to-access and in-depth guide in the latest diagnostic and treatment options for this complicated and challenging disease, and will be an important resource for all medical professionals who manage or may encounter this challenging group of patients.